2008
DOI: 10.1074/jbc.m802074200
|View full text |Cite
|
Sign up to set email alerts
|

The Preference of Tryptophan for Membrane Interfaces

Abstract: To better understand the structural and functional roles of tryptophan at the membrane/water interface in membrane proteins, we examined the structural and functional consequences of Trp 3 1-methyl-tryptophan substitutions in membranespanning gramicidin A channels. Gramicidin A channels are miniproteins that are anchored to the interface by four Trps near the C terminus of each subunit in a membrane-spanning dimer. We masked the hydrogen bonding ability of individual or multiple Trps by 1-methylation of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 73 publications
9
76
1
Order By: Relevance
“…Even very short tryptophancontaining peptides can associate with lipid bilayers (45). The lipid-binding motif of y1fatc contains two conserved, sequentially close tryptophans (Trp-2466 and Trp-2470) that may be critical determinants for the affinity and specificity of membrane association.…”
Section: Derivation Of a Model Of The Micelle Association Of Oxidizedmentioning
confidence: 99%
See 1 more Smart Citation
“…Even very short tryptophancontaining peptides can associate with lipid bilayers (45). The lipid-binding motif of y1fatc contains two conserved, sequentially close tryptophans (Trp-2466 and Trp-2470) that may be critical determinants for the affinity and specificity of membrane association.…”
Section: Derivation Of a Model Of The Micelle Association Of Oxidizedmentioning
confidence: 99%
“…The y1fatc Mutants W2466A and W2466A/W2470A Still Bind DPC Micelles-Tryptophans play an important role for the interaction of many membrane proteins with lipid bilayers and often favor a position at the interface of the aqueous solution and the lipid phase (45,46). Even very short tryptophancontaining peptides can associate with lipid bilayers (45).…”
Section: Derivation Of a Model Of The Micelle Association Of Oxidizedmentioning
confidence: 99%
“…Tryptophan-rich AMPs such as indolicidin and tritrpticin have been shown to insert into membranes, and partition near the membrane-water interface, enabling the peptide to anchor to the bilayer surface, however this motif has been little investigated in SMAMPs. 66 , 67 A tryptophanlike indole monomer, 2-(1H-indol-3-yl)ethyl methacrylate (IEMA), was incorporated into two tryptophan mimicking series -one with a lysine mimic cation source (aminoethyl methacrylate -AEMA; poly(AEMA-IEMA), and the other with an arginine mimic cation source (2-guanidinoethyl methacrylate -GEMA; poly(GEMA-IEMA.) 68 These polymers were evaluated against S. epidermidis and the methicillin-resistant strain of S. aureus for their antimicrobial activity.…”
Section: Fig (23) β-Lactam Monomers Used In Studymentioning
confidence: 99%
“…12,13 NMR studies on indole derivatives embedded in lipid bilayers have 40 demonstrated that the dipole moment of the indole group, cation-π interactions and the ability of the indole group to participate in hydrogen bonding interactions with lipids all contribute to localisation in the interfacial region. 11,[14][15][16] More recently however, steric effects and dipole-dipole 45 contributions have been suggested to be more important than hydrogen bonding or cation-π interactions for determining the membrane partitioning and alignment of these and related indole derivatives. 10 Molecular dynamics simulations of mixed indole-lipid and tryptophan-lipid systems indicate a 50 preference for indole to localise at specific locations in relation to membranes, including the middle of the bilayer, proximal to the choline headgroup and in the region of the lipid carbonyl groups, with the latter being the preferred site.…”
Section: Introductionmentioning
confidence: 99%
“…Important enthalpic factors are likely to include electrostatic interactions involving the indole side-chain, such as cation-π interactions and hydrogen bonds, 35 alongside contributions arising from peptide conformational changes and dipolar interactions with membrane lipids. 10,11 Entropic factors include perturbation of lipid and bilayer structure, as well as the hydrophobic effect. 12,13 NMR studies on indole derivatives embedded in lipid bilayers have 40 demonstrated that the dipole moment of the indole group, cation-π interactions and the ability of the indole group to participate in hydrogen bonding interactions with lipids all contribute to localisation in the interfacial region.…”
Section: Introductionmentioning
confidence: 99%